The Influence of Interactive Media Flashcards on the Process of Memorizing the Qur'an in Early Childhood - Liana; Trisya Sumiati; Yohanes Bahari; Warneri (Attractive : Innovative Education Journal, 2024)
This research aims to examine the effect of using interactive media in the form of "flashcards" on the process of memorizing the Al-Qur'an in early childhood at the Tahfidz Darul Quran Al Haramain Islamic Boarding School. The research method used was quantitative with a quasi-experiment approach involving two groups, namely the experimental group given flashcard media and the control group without this media. The research sample consisted of 40 young children who were divided randomly into each group. The results of the study showed that the use of flashcards had a significantly positive effect on the ability to memorize the Al-Qur'an in young children, as indicated by a higher increase in memorization scores in the experimental group compared to the control group. Flashcard interactive media makes it easier for children to remember verses using attractive visuals and effective repetition, thereby increasing motivation and focus in the memorization process. This research concludes that flashcard media can be an effective tool in supporting memorizing the Al-Qur'an in early childhood in the Islamic boarding school environment. The recommendation from this research is that tahfidz educational institutions consider using similar interactive media to improve learning outcomes in memorizing the Koran for children.